Extensive aortic surgery in acute aortic dissection type A on outcome: insights from 25 years single center experience - Dib, Bashar; Seppelt, Philipp; Arif, Rawa; Weymann, Alexander; Veres, Gábor; Schmack, Bastian; Beller, Carsten J.; Ruhparwar, Arjang; Karck, Matthias; Kallenbach, Klaus (Journal of cardiothoracic surgery, 2019)
This single center study compares the different surgical techniques used in the treatment of acute aortic dissection type A (AADA) analyzing the influence of the extent of the surgical approach on outcome.